Relationship between long working hours and smoking behaviors: Evidence from population-based cohort studies in Korea - Baek, Seong-Uk; Lim, Myeong-Hun; Kim, Taeyeon; Lee, Yu-Min; Won, Jong-Uk; Yoon, Jin-Ha (Scandinavian Journal of Work, Environment & Health, 2024)
' ' OBJECTIVES ': 'Long working hours and overwork are growing public health concerns in the Western-Pacific region. We explored the relationship between working hours and smoking behaviors of Korean workers. ' ' METHODS ': 'This study included 284 782 observations (50 508 workers) from four nationwide cohort studies in Korea. Using generalized estimating equations, we estimated the associations of working hours with current smoking status, smoking initiation, and smoking cessation within each cohort. Cohort-specific estimates were combined through random-effect meta-analysis. Effect sizes were presented as odds ratios (OR) and 95 confidence intervals (CI). ' ' RESULTS ': 'The overall smoking prevalence was 26.8% within the cohorts. The adjusted OR (95% CI) of the association between working hours and current smoking were 1.01 (0.94–1.08) for <35 hours/week, 1.04 (1.01–1.09) for 41–48 hours/week, 1.06 (1.01–1.10) for 49–54 hours/week, and 1.07 (1.04–1.10) for ≥55 hours/week compared with 35–40 hours/week. The adjusted OR (95% CI) of the association between working hours and smoking cessation in the follow-up were 0.93 (0.85–1.02) for <35 hours/week, 0.89 (0.83–0.96) for 41–48 hours/week, 0.87 (0.81–0.95) for 48–54 hours/week, and 0.91 (0.85–0.98) for ≥55 hours/week compared with 35–40 hours/week. No clear associations were observed between working hours and smoking initiation. ' ' CONCLUSION ': 'Long working hours are associated with high current smoking risk and reduced likelihood of smoking cessation among Korean workers. Policy interventions are required to promote smoking cessation and reduce excess overwork for individuals experiencing long working hours.
Keywords: health behavior; health-related behavior; Korea; lifestyle; long working hour; nicotine; overtime work; overwork; population-based cohort; smoking; tobacco; working hour; working time